2020
DOI: 10.3340/jkns.2019.0067
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Aneurysm after Treatment Using Flow Diverter Stent : Histopathological Study in Experimental Canine Carotid Side Wall Aneurysm

Abstract: Objective : Despite widespread use of flow diverters (FDs) to treat aneurysms, the exact healing mechanism associated with FDs remains poorly understood. We aim to describe the healing process of aneurysms treated using FDs by demonstrating the histopathologic progression in a canine aneurysm model. Methods : Twenty-one side wall aneurysms were created in common carotid artery of eight dogs and treated with two different FDs. Angiographic follow-ups were done immediately after placement of the device, 4 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…We reiterate that the enhancement patterns described herein arise from presently indeterminate sources, but considering their nearly ubiquitous nature, and their discordance with angiographic occlusion, we believe they might represent a combination of healing effects/endothelialization within and around the aneurysm sac, and potentially the formation of nascent vascular channels, vascularized tissues, or less probably, vasa vasorum recruitment associated with the thrombosed component of the aneurysm, as have been reported in past histological studies 23–25. The timeline for development of these findings following treatment, or to what extent they may have existed prior to treatment, are not conclusively assessed in our cohort owing to the absence of consistent pretreatment VWI, as well as the variable post-treatment durations before VWI is carried out.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…We reiterate that the enhancement patterns described herein arise from presently indeterminate sources, but considering their nearly ubiquitous nature, and their discordance with angiographic occlusion, we believe they might represent a combination of healing effects/endothelialization within and around the aneurysm sac, and potentially the formation of nascent vascular channels, vascularized tissues, or less probably, vasa vasorum recruitment associated with the thrombosed component of the aneurysm, as have been reported in past histological studies 23–25. The timeline for development of these findings following treatment, or to what extent they may have existed prior to treatment, are not conclusively assessed in our cohort owing to the absence of consistent pretreatment VWI, as well as the variable post-treatment durations before VWI is carried out.…”
Section: Discussionsupporting
confidence: 55%
“…The highly effective flow suppression provided by DANTE coupled with variable flip-angle 3D turbo spin echo makes the presence of insufficient flow suppression or artifacts from the metallic construct unlikely despite the well-recognized vulnerability of historic VWI techniques. Because of the persistence of insufficient flow suppression, even in treated aneurysms without residual flow by DSA,30 we would consider possible explanations to be the ongoing cascade of mural inflammation, organizing intra-aneurysmal thrombosis, neointimal angiogenesis, and vasa vasorum recruitment within the adventitia23…”
Section: Discussionmentioning
confidence: 99%
“…The flow diverter gradually occludes an aneurysm within an organized thrombus by enhancing an intra-aneurysmal flow diversion 24 and neointima formation. 25 Consequently, flowdiverter treatment has a lower probability of recurrence than conventional coiling, even in lesions vulnerable to recurrence. Therefore, a flow diverter might be a better treatment option for recurrent aneurysms even after SAC.…”
Section: Discussionmentioning
confidence: 99%
“…All early delayed rupture cases were located in the distal internal carotid artery, and the patient finally died. To avoid this fatal complication, several techniques including adjunctive coil insertion and strict blood pressure (BP) control have been suggested [16,23,26]. Erez et al reported that pipeline embolization device with partially dense coil packing showed high complete occlusion rate (23 of 27 patients, 85.2%) without delayed rupture at 1-year follow-up [21].…”
Section: Discussionmentioning
confidence: 99%